Trail to Cottonwood Falls : A Ralph Compton Novel - Richards, Dusty (New York A Signet Book, 2007)
Taking one last chance to prove himself, former cowboy and Ranger Ed Wright takes on the task of driving a herd of cattle from Texas to Kansas, but must contend with a rival outfit that is determined to see him fail.
Keywords: Cattle drives -- United States--Texas Cattle Trail